Toxicity effects of reflectin nanoparticles in keratinocyte cells - Lim, Felicia Jia Jia (Nanyang Technological University, 2023)
UV radiation has been proven to be detrimental to health due to genotoxicity. To mitigate this, sunscreen was developed with compounds that could absorb, reflect, or scatter UV radiation. Over the past decades, nanoparticles have been used in sunscreen formulations to reduce the white cast while providing more effective absorption or scattering of UV radiation. However, the long-term side effects of applying sunscreen formulated with nanoparticles such as TiO2 and ZnO are largely unknown. These safety concerns have led to a need to find an alternative biocompatible UV filter that utilises biomaterial and has similar or lower toxicity than metal oxides. In this project, the cytotoxicity of Sepioteuthis lessoniana reflectin nanoparticles in keratinocyte cells and the UV absorbance of the conjugated SIRF nanoparticles were evaluated as a potential biocompatible UV filter.